Accuracy as complex display of psychomotor functions - Козина, Ж. Л.; Середа, О. А. (Physical Education Theory and Methodology, 2013)
In work results of definition of quantitative interrelation of accuracy of throws from an average distance and penal throws with more than 30 parameters of pedagogical, physiological, psychological, medical testing are submitted. The received data have allowed to draw a conclusion that accuracy of throws in basketball is the complex quality dependent on a degree of a coordination of action cardiovascular, nervous and other systems of an organism.